Analisis Sumber Daya Manusia Pendidikan Tinggi - Ida Kintamani DH (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this analysis is to understand the Higher Education (HE) Human Resources profile and quality, and determine the quality of HE by using the 2009/2010 data. The method used in this analysis is the documentation study and the survey. In addition, the use of key performance indicators from Education Strategic Plan 2010-2014 to assess the quality of HE. Results showed that although private institutions have reached 97.24% of HE, it only has 58.39% of the students and 71.83% lecturers. Based on 7 indicators, feasibility of lecturers to teach only 37.65%, full-time professors 67.82%, lecturers professors 3.59%, senior lecturer 19.84%, and most education personnel are high school graduated which is 34.82%. Based on the selected five composite indicators, the quality of PT is only 49.85 means that less than half. By looking at the results, they are advised to conduct further research regarding collection of data about the HE, especially teachers with all the details and whether the composite indicators used are appropriate to measure the quality of HE.Â ABSTRAKTujuan analisis SDM PT adalah untuk memahami profil SDM PT, mutu SDM PT, dan menentukan mutu PT dengan menggunakan data tahun 2009/2010. Metode yang digunakan dalam analisis ini adalah studi dokumentasi dan survai. Selain itu, digunakan indikator kinerja utama (IKU) dari Rencana Strategi Pendidikan tahun 2010-2014 untuk menilai mutu PT. Hasilnya menunjukkan bahwa walaupun lembaga PT Swasta sebesar 97,24% dari lembaga PT yang ada, namun mahasiswanya hanya sebesar 58,39% dan dosennya sebesar 71,83%. Berdasarkan 7 indikator, kelayakan dosen mengajar hanya 37,65%, dosen tetap sebesar 67,82%, dosen jabatan guru besar sebesar 3,59%, dosen senior sebesar 19,84%, dan tenaga kependidikan kebanyakan lulusan SM sebesar 34,82%. Berdasarkan 5 indikator komposit yang dipilih maka mutu PT hanya sebesar 49,85 berarti kurang dari separuh. Dengan melihat hasil seperti ini maka disarankan agar dilakukan penelitian lanjutan mengenai pendataan PT khususnya dosen dengan semua rinciannya dan apakah indikator komposit yang digunakan telah sesuai untuk mengukur mutu PT